Identification of opaque 2 (o-2) gene In Crossing Between Madura’s Local Maize (Zea mays L. cv. Guluk-guluk) and Quality Protein Maize (Z. mays L. cv. Srikandi kuning) - Daryono, Budi Setiadi; Rofiah, Oktiviani (2009)
Maize (Zea mays L.) is one of the main foods instead of rice in Indonesia. Generally, amino acid of lysin and tryptophan content in maize is low. Maize production in Indonesia has been increasing but its production is still low. Many efforts have been applied to enhance the maize production through breeding. However, breeding of a Madura’s local maize (Guluk-guluk) with a Quality Protein Maize (Srikandi kuning) has not been conducted. In maize, opaque 2 gene (o-2 gene) is a ressecive gene and could be regulate a number of enzymes of glycolysis and ricarboxylic acid pathway,egulates and reduces zein gene expression, influencing ask1 and ask2 gene which encode of lysin and threonin synthesis.Hence, the gene has been increase of amino acid of lysin and triptophan particularly. The research was carried out to study the inheritance of o-2 gene in crossing between Guluk-guluk and Srikandi kuning. The research was started by crossing between Guluk-guluk and Srikandi kuning to obtain F1, F2 and back cross populatin. The DNA maize was isolated and its DNA quality was determined by electrophoresis on 2% agarose gel. Polymerase Chain Reaction (PCR) was applied to detect o-2 gene in maize. Based on the results of detection of o-2 gene, it could be revealed that the inheritance of o-2 gene in maize follows the Mendel law and controlled by a single recessive gene.